Intuition in Islamic and Contemporary Psychology - Rihab Said Aqil; Abdul Mujib (JURNAL INDO-ISLAMIKA, 2022)
In the last two decades, the theme of intuition has increasingly attracted the attention of academics, including psychologists. The increasing interest of psychologists in intuition is because the process of judgment and decision-making within individuals often occurs outside of their conscious thinking. This happens when individuals face uncertain situations, time pressure, and complex, ambiguous, and even strange problems. Intuition is the capacity of the human soul to know or understand a matter automatically, effortless, and affectively without rational processes. Intuition in psychological studies is based on experiences and knowledge accumulated from the past and stored in memory. In contrast to the Islamic perspective, intuition (divine) is based on the experience of spiritual disclosure coming from divine gifts. This study uses a psychological approach with descriptive comparative analysis techniques to discuss intuition, its mechanisms and development, originating from two perspectives: Islam and contemporary psychology. This study constructs five types of intuition where spiritual intuition occupies the highest position, followed by moral, creative, expertise, and social intuition.